Combined approach architecture development to simulation modeling of systems with parallelism - Suprunenko, Oksana (Eastern-European Journal of Enterprise Technologies, 2021)
Paradigms and graphical-analytical tools for building simulation tools and forming the architecture of a combined approach to studying the dynamic properties of systems with parallelism are described. An extension of the formal language of Petri nets is presented, which has greater modeling power than WF nets. The properties of hierarchical Petri nets are used to synthesize a holistic model. Discrete-event modeling and modeling of dynamic systems, which allow reflecting the quantitative and qualitative characteristics of the elements of the systems under study, served as the basis for the combined approach to the simulation of systems with parallelism. On their basis, graphic-analytical tools are proposed that provide the ability to describe the modeled system, adhering to the principle of structural similarity. They have dynamic simulations that make it easy to visually analyze and correct the model. Also, the proposed toolkit provides for the analysis of the dynamic properties of the model, which makes it possible to identify accumulated phenomena that can lead to unpredictability of the system’s functioning. A conceptual model for the synthesis and analysis of systems with parallelism is proposed, which provides for the construction of the components of the model based on the architecture. Their step-by-step analysis and the formation of an integral model of the software system are carried out using a network representation, according to the matrix description of which invariants are calculated. The analysis of invariants allows one to obtain the dynamic properties of the model and determine the localization of structures that lead to critical situations when they are detected. The architecture of the combined approach to the simulation of systems with parallelism is built, which provides the study of their dynamic properties to improve the reliability of the functioning of software systems